EFEKTIVITAS CITY BRANDING “NEGERI INDAH KEPINGAN SURGA” TERHADAP KUNJUNGAN WISATAWAN KE KABUPATEN SAMOSIR - Nasution, Ridwan; Parhusip, Lasdame (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT The concept of city branding is a strategy studied to introduce a region to the public. The important thing in this branding is to change the mindset and view of a city. The Regional Government of Samosir Regency established a branding that is considered capable of introducing the potential of the region with the tagline " Negeri Indah Kepingan Surga” (Wonderfull Land Piece of Paradise). The city branding developed is prepared for local, domestic and international markets. The purpose of this research is to determine the effectiveness of city branding " Negeri Indah Kepingan Surga " on visitor interest to Samosir Regency. The research approach used is descriptive qualitative. With a descriptive qualitative method with data collection techniques through observation, literature research and interviews or interviews with informants of visitors at three tourist attractions (Holbung Hill, Sibea-Bea Hill and Pusuk Buhit) and the Head of the Promotion Section of the Samosir Regency Tourism and Culture Office. The results of the research on the effectiveness of city branding "Negeri Indah Kepingan Surga" on tourist visits to Samosir Regency have not been maximized on target and still need to be improved, especially in the provision of facilities and infrastructure and changing the target market. The obstacles that occur in the implementation of the effectiveness of city branding include the lack of community participation in improving tourism in Samosir. Keywords: City Branding; Samosir; Tourist; Tourism Communication